Digital Transformation of Tax and Customs Administrations - Junquera-Varela, Raul Felix (Washington, DC: World Bank, 2022)
Domestic resource mobilization has become a core priority of the sustainable development agenda for tax and customs administrations. Information systems can play a critical role in revenue mobilization, which may create the much-needed fiscal space for maneuver and allow for more spending on all the things that drive potential growth over the medium term. New technologies can also increase the effectiveness of the internal operations of tax and customs administrations, and can reduce costs, as they improve their capacity to collect revenue with smarter use of the information they collect. Of particular interest is machine learning, which can be used to solve difficult problems that arise from the inability of revenue administrations to process massive amounts of data efficiently. Technology by itself can only provide tools. To achieve meaningful and impactful goals, a comprehensive strategy must be defined, covering the regulatory, institutional, and operational aspects. This paper analyzes such aspects and provides a roadmap for policymakers and tax officials on how to incorporate and manage disruptive technologies into the process of building the tax and customs administrations of tomorrow.